A newly designed duodenoscope with detachable distal cap significantly reduces organic residue contamination after reprocessing - Ridtitid, Wiriyaporn; Pakvisal, Piyapoom; Chatsuwan, Tanittha; J. Kerr, Stephen; Tiankanon, Kasenee; Piyachaturawat, Panida; Mekaroonkamol, Parit; Kongkam, Pradermchai; Rerknimitr, Rungsun (Endoscopy, 2020)
Background A newly designed duodenoscope with detachable distal cap may reduce bacterial contamination by allowing better access to the elevator. We compared bacterial contamination and organic residue evaluated by rapid adenosine triphosphate (ATP) test and culture from duodenoscopes with detachable vs. fixed distal caps after high-level disinfection (HLD).Methods During December 2018–April 2019, 108 used newly designed duodenoscopes were enrolled. In group A (n = 54), the distal cap of the duodenoscope was detached before manual cleaning. In group B (n = 54), the distal cap was not detached. After HLD, samples were collected from the elevator, submitted for culture, and evaluated using the ATP test, using the cutoff value of 40 relative light units (RLUs).Results After HLD, the proportion of potential bacterial contamination and organic residue in group A was significantly lower than in group B (37.0 % vs. 75.9 %; P  < 0.001; relative risk 0.49, 95 % confidence interval 0.33–0.71), and also confirmed by median ATP values (45.2 vs. 141.0 RLU; P  < 0.001). In group B, one sample culture was positive for nonpathogenic bacteria. Pathogenic bacteria were not found in any culture from either group.Conclusions The detachable distal cap was more effective at eliminating bacterial contamination and reducing organic residue than a fixed cap. Nonpathogenic bacteria were detected in the fixed cap group after reprocessing. The ATP test with 40 RLU cutoff is a practical method to ensure the cleanliness of duodenoscope reprocessing without the need to wait for bacterial culture results.